(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
Development of the stock market through Islamic securities in the conditions of the digital economy and the prospects of using green energy as an alternative option for energy resources are one of the current topics in the financial system today. Therefore, during the research, extensive work was carried out within the scope of the topic. Among other things, other research works on the topic, opinions of local and foreign scientists, scientific articles, and local normative documents on the topic were studied. In order to increase the practical significance of the scientific work, international Islamic finance and Islamic securities were studied based on statistical data in scientific journals. Based on the studied and analyzed data, Islamic securities in the development of the stock market in the digital economy. Scientific and practical conclusions and proposals have been developed on the prospects of the people.